Actinomycotic osteomyelitis of palate masquerading periapical pathology: A rare case report - Prachi Baldawa; Pallavi Shirol; Dinraj Kulkarni; Supriya Koshti; Nitu Mishra (Wolters Kluwer Medknow Publications, 2018)
Osteomyelitis is an infection that is challenging to manage due to the poor vascularization of bone that favors the proliferation of microorganisms. We report a case of osteomyelitis occurring in endodontically treated teeth in the maxillary palatal region. Clinically and radiographically, it was initially diagnosed as osteomyelitis and was treated accordingly with antibiotics for 1 year with no reported healing. Later, biopsy was done and the findings were consistent with that of chronic osteomyelitis in association with infection by Actinomyces organisms. Thus, the case highlights the rare occurrence of actinomycotic osteomyelitis in maxilla and the importance of biopsy and histopathology which will help in correct diagnosis and rapid resolution through appropriate antibiotic therapy.